Online High Performance Liquid Chromatography (HPLC)-ABTS(+) Based Assay and HPLC-Electrospray Ionization Mass Spectrometry Analysis of Antioxidant Phenolic Compounds in Salsola komarovii - Lee, Hee Ju; Pan, Cheol-Ho; Kim, Eun-Sil; Kim, Chul Young (KOREAN SOC APPLIED BIOLOGICAL CHEMISTRY, 2012)
Online high performance liquid chromatography (HPLC)-2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS(+)) based assay system for phenolic antioxidants in Salsola komarovii extracts was applied. HPLC elute was mixed with a stabilized solution of ABTS+ reagents, and the negative peaks, indicating the antioxidant activity, were monitored by measuring the decrease in absorbance at 734 nm. HPLC with electrospray ionization mass spectrometry was used to identify the seven flavonoids and two phenolic amides in the S. komarovii extracts. The antioxidant compounds were identified as rutin, isoquercitrin, astragalin, and isorhamnetin.
Keywords: LC-MS; PLANT